The Influence of Work Environment, Work Discipline and Work Motivation on Employee Performance: JEL Classification: M12; M54; O15; J24; J28 - Khairul Latif; Muh. Syakil (Maroon Journal De Management, 2026)
This study aims to analyze the influence of work environment, work discipline, and work motivation on employee performance at PT Intan Sejahtera Abadi, Indonesia. Employee performance has become an important issue in organizational sustainability, particularly in labor-intensive companies that rely heavily on operational workforce productivity. This research employed a quantitative causal approach using a saturated sampling technique involving 100 employees as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 27. The findings reveal that work environment, work discipline, and work motivation each have a positive and significant effect on employee performance. Simultaneously, the three variables collectively contribute significantly to explaining employee performance variation within the organization. Work discipline emerged as the most dominant predictor, indicating the importance of organizational compliance and behavioral regulation in improving productivity. The novelty of this study lies in its integrated examination of organizational and motivational factors within a medium-sized Indonesian private-sector company dominated by operational employees. The findings provide theoretical contributions to human resource management literature and practical implications for organizations seeking to improve employee productivity through integrated managerial strategies.